The importance of nontradable goods' prices in cyclical real exchange rate fluctuations - Burstein, Ariel T. 1974-; Eichenbaum, Martin S. 1954-; Rebelo, Sérgio 1959- (National Bureau of Economic Research, 2005)
"Changes in the price of nontradable goods relative to tradable goods account for roughly 50 percent of the cyclical movements in real exchange rates"--National Bureau of Economic Research web site.
Keywords: Ökonometrisches Modell; Foreign exchange rates -- Econometric models